2022
DOI: 10.1021/acs.biochem.2c00320
|View full text |Cite
|
Sign up to set email alerts
|

Water Leakage Pathway Leads to Internal Hydration of the p53 Core Domain

Abstract: The gene encoding the p53 tumor suppressor protein is the most frequently mutated oncogene in cancer patients; yet, generalized strategies for rescuing the function of different p53 mutants remain elusive. This work investigates factors that may contribute to the low inherent stability of the wild-type p53 core domain (p53C) and structurally compromised Y220C mutant. Pressure-induced unfolding of p53C was compared to p63C, the p53 family member with the highest stability, the engineered superstable p53C hexamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…These molecules have progressed to preclinical or clinical trials (CTs). More recent studies using hydrostatic pressure and molecular dynamics simulations have identified dehydrons on the surface of the p53 DBD, i.e., vulnerable sites related to p53 misfolding and aggregation. , These vulnerable regions represent novel targetable sites to stabilize and avoid p53 misfolding.…”
Section: Strategies To Target Misfolded P53 Mutant P53 Aggregation An...mentioning
confidence: 99%
“…These molecules have progressed to preclinical or clinical trials (CTs). More recent studies using hydrostatic pressure and molecular dynamics simulations have identified dehydrons on the surface of the p53 DBD, i.e., vulnerable sites related to p53 misfolding and aggregation. , These vulnerable regions represent novel targetable sites to stabilize and avoid p53 misfolding.…”
Section: Strategies To Target Misfolded P53 Mutant P53 Aggregation An...mentioning
confidence: 99%
“…100 There are also studies that have underscored the impact of water leakage into the hydrophobic core on p53C. 67 In this context, we tried to investigate how the cavity-enlarging shift of the β-hairpin S2–S2′ affects the hydrophobic core, thereby promoting the reduction in thermal stability and the increase in aggregation propensity of R248W p53C.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ADH-6 inhibits the aggregation of R248W p53 in human cancer cells, restoring the transcriptional activity of p53, leading to cell cycle arrest and apoptosis. 19 Molecular dynamics (MD) simulations have been extensively employed to investigate the conformational properties of different domains of the p53 protein and its mutants, 41,42,[63][64][65][66][67][68][69] as well as the interactions between p53 protein domains and small molecules, 70 short peptides, 71 and other proteins. [72][73][74][75] In spite of experimental and computational studies, it remains mostly unknown how the R248W mutation induces destabilization of R248W p53C and how ADH-6 stabilizes R248W p53C.…”
Section: Introductionmentioning
confidence: 99%